Coronavirus Pandemic: a major public health crisis for the developed and developing world - Rooh Ullah; Muhammad Suleman Rana; Mehmood Qadir; Muhammad Usman; Niaz Ahmed (Journal of Infection in Developing Countries)
Pandemic of novel Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infections in China is now become global public health crisis. At present 87.64% of the world is infected by this deadly illness. The risk from this epidemic depends on the nature of the virus, including how well it transmits from person to person, and the complications resulting from this current illness. The novel coronavirus has killed thousands of people in China and other countries as well; its rate of mortality is increasing day by day. There is an urgent need to control the virus by developing vaccine or any other antiviral drugs to save the world from this deadly viral infection.